On models with wobbling disk for brake squeal - Nguyen Thai Minh, Tuan; Gräbner, Nils (Vietnam Journal of Science and Technology, 2021)
Among many mathematical models of disk brakes for the explanation of brake squeal, models with wobbling disk have their own advantage over planar models. Applying a recently developed matrix form of Euler equations in rigid body dynamics, the equations establishment process can now be performed with almost all popular computing software. Furthermore, the presented models are more generalized in terms of damping, in-plane vibration, and unsymmetrical mounting.